Complications Associated with Continuous RRT. Issue 11 (24th November 2022) - Gautam, Samir C.; Lim, Jonathan; Jaar, Bernard G.
Abstract : Continuous renal replacement therapy (CRRT) is a form of renal replacement therapy that is used in modern intensive care units (ICUs) to help manage acute kidney injury (AKI), end stage kidney disease (ESKD), poisonings, and some electrolyte disorders. CRRT has transformed the care of patients in the ICU over the past several decades. In this setting, it is important to recognize CRRT-associated complications but also up-to-date management of these complications. Some of these complications are minor, but others may be more significant and even life-threatening. Some CRRT complications may be related to dialysis factors and others to specific patient factors. Our overarching goal in this article is to review and discuss the most significant CRRT-related complications at the different stage of management of CRRT. With the advent of newer solutions, there have been newer complications as well.